Chocolate In Jar Sebagai Variasi Produk Dessert Jar Bernutrisi - Budiman, Johny; Andarini, Retno; Sofia, Sofia; Sugandi, Dwinta; Tiara. C, Indah; Ainabila, Salsa Siti (LPPM Universitas Internasional Batam, 2023)
The era of globalization which offers a lot of instant food. Unknowingly, excessive sugar consumption in the long term can trigger many health problems such as obesity and diabetes mellitus. Chocolate in jarâ€ is a dessert tha tbeen developed with a sweet taste using clear jar packaging but still safe for consumption. A practical culinary dish with attractive visuals and also a premium chocolate taste and contains gluten free and sugar free which we combine with rice crispy. Product Itâ€™s also inspired and covers 2 of the 17 Sustainable Development Goals (SDGs). The Goals are built on the important principle of leaving no one behind, and emphasizing a holistic approach to achieve sustainable development for all.